81Kr dating of 1 kg Antarctic ice - F. Ritterbusch; J. S. Wang; X. Feng; S. Shackleton; M. Bender; E. Brook; J. Higgins; Z.-H. Jia; W. Jiang; Z.-T. Lu; J. P. Severinghaus; L.-T. Sun; et al. (Nature Communications)
Abstract Recovering earth’s climate history from ice cores requires reliable dating of the ice. 81Kr is ideal for radiometric dating up to more than one million years, but the isotope is so rare that it has long been a challenge to apply 81Kr dating on ice cores where sample size is limited. Here, we show 81Kr dating of 1-kg ice-core samples from Taylor Glacier, Antarctica. This is made possible by an advance in 81Kr detection with an all-optical realization of Atom Trap Trace Analysis. The achieved sample-size reduction facilitates 81Kr dating of basal ice-core sections with direct implications for open questions in paleoclimatology, such as the evolution of glaciers on the Tibetan Plateau or the stability of the Greenland and West-Antarctic ice sheets.